TAX EVASION IN DOMESTIC AND COMPARATIVE CRIMINAL LAW - Coković, Sabahudin Z (Poslovna ekonomija, 2017)
Tax evasion is one of the most serious crimes against the economy, which is directed directly against the fiscal system of the state, but also a crime that is almost usually exercised in the field of economic crime. In view of the above, the paper deals with the concept and the basic elements of tax evasion, as well as a separate crime against the economy. The first part is dedicated to the definition of concepts and elements of the criminal offense of tax evasion in particular to available comparative criminal legislation, namely: the Republic of Albania, the Republic of Finland, the Republic of Croatian, Russian Federation and the Federal Republic of Germany, while in the second part of the attention paid to determining the concept, elements and basic characteristics of the criminal offense of tax evasion in the positive criminal legislation of the Republic of Serbia.